Current distribution of Phelsuma inexpectata, a threatened Réunion Island endemic gecko - Mickaël Sanchez; Alicia Bonanno; Margot Caubit; Alice Bousseyroux; Johanna Clémencet (Oryx)
The Manapany day gecko Phelsuma inexpectata is a Critically Endangered species endemic to Réunion Island in the Indian Ocean. Studying its geographical distribution and its evolution is important for developing effective biodiversity conservation strategies. We evaluated past and current distributions of P. inexpectata using records from 2008–2020 and through recent, intensive field surveys (230 person-days, 2020–2022). We found that its past distribution has declined by more than 28% (5.12 ha), from 19.44 ha to 14.32 ha. In natural habitats, the distribution of P. inexpectata has been strongly affected, declining by c. 45%, but we identified new areas of occurrence (10.72 ha) through field surveys. Most of these new areas (79%) were found in anthropogenic habitats where the species had not been documented before. The current distribution of P. inexpectata covers c. 24 ha, of which 75% is located in urban areas such as gardens and green urban spaces. Moreover, our field survey showed that at least 10% of its range is now colonized by the invasive gold-dust day gecko Phelsuma laticauda. This survey provides an essential baseline for tracking the future distribution of this threatened species and its potential invasive competitor, and for monitoring how changes to its habitat affect the distribution of P. inexpectata.